2018
DOI: 10.1108/ijopm-03-2017-0162
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and exploitation within supply networks

Abstract: Purpose The purpose of this paper is to introduce and define the concept of purchasing ambidexterity in terms of two dimensions: balance dimension and combined dimension. The study proceeds to empirically examine the multiple performance effects generated for the buying firm and its key suppliers. Design/methodology/approach Ambidexterity theory informs the authors’ conceptual model. To test the hypotheses, the authors collected survey data from 95 purchasing functions of medium and large European firms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 67 publications
1
33
0
1
Order By: Relevance
“…Particularly, exploitation objectives to enhance the existing materials or technologies, while the exploration is to collect and diverse new information and knowledge to systematized organizations ( Guan and Liu, 2016 ; Lavie et al, 2010 ; Phelps, 2010 ; Yan and Guan, 2018 ). Prior studies have designedly preferred to assess the combined effect of exploration and exploitation on firm performance ( Uotila et al, 2009 ; Gualandris et al, 2018 ; Bravo et al, 2018 ). Sahi et al (2020) measure the strategic orientation effects, such as market and business tactical positioning, on operational exploitational and explorational ambidexterity for improving business performance and found that small and medium firms’ entrepreneurial and market orientations has greater prominence on explorative operational activities, and exploitative operational activities has high impacts on entrepreneurial orientation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Particularly, exploitation objectives to enhance the existing materials or technologies, while the exploration is to collect and diverse new information and knowledge to systematized organizations ( Guan and Liu, 2016 ; Lavie et al, 2010 ; Phelps, 2010 ; Yan and Guan, 2018 ). Prior studies have designedly preferred to assess the combined effect of exploration and exploitation on firm performance ( Uotila et al, 2009 ; Gualandris et al, 2018 ; Bravo et al, 2018 ). Sahi et al (2020) measure the strategic orientation effects, such as market and business tactical positioning, on operational exploitational and explorational ambidexterity for improving business performance and found that small and medium firms’ entrepreneurial and market orientations has greater prominence on explorative operational activities, and exploitative operational activities has high impacts on entrepreneurial orientation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it is argued there is pressure between exploitation and exploration valuable ground found in environmental sustainability since ambidextrous operations require cross-border decision strategies to deal with the external environment changes with the internal resources and capabilities supports. Gualandris et al (2018) claimed small firms are better with enhanced exploration rather than balancing the two dimensions in rapidly changing SC environment with technologies, policies, and market requirements. Zhao et al (2021) argued that exploratory innovation not only reserves and enriches the existing knowledge, but also generates new materials or technologies compared with the exploitative innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, purchasing is increasingly also contributing to new technology scouting and sourcing (Lakemond Echtelt, and Wynstra 2001;Legenvre and Gualandris 2018), mobilizing supplier resources (Ellegaard and Koch 2012) and facilitating early supplier involvement in new product development (Schiele 2010). Gualandris et al (2018) conceptualise purchasing ambidexterity as a contextual capability. They argue that 'for higher levels of ambidexterity, purchasing personnel will be allowed to make their own (contextual) judgments on how to best advance and balance efficiencyoriented and innovation-oriented activities' (Gualandris et al 2018, 672).…”
Section: Purchasing's Role In Oamentioning
confidence: 99%